FRI0249 Risk Factors for Development of Pulmonary Arterial Hypertension in Australian Scleroderma Patients. (15th July 2016) - Morrisroe, K.; Huq, M.; Stevens, W.; Rabusa, C.; Proudman, S.; Nikpour, M.; ,
Abstract : Background: Pulmonary arterial hypertension (PAH) is the leading cause of mortality in patients with scleroderma (SSc). Objectives: To determine the incidence, prevalence and risk factors for PAH development in a large Australian SSc cohort. Methods: PAH was diagnosed on right heart catheterization (mPAP >25 and PAWP <15 mmHg at rest). Patients with PH secondary to interstitial lung disease (ILD; defined as abnormal HRCT scan and FVC<60%) were excluded. Summary statistics, chi-square tests, univariate and multivariable logistic regression along with post-estimation diagnostics were used to determine the associations of different combinations of risk factors with PAH. Results: Among 1579 SSc patients, 8.4% (132 patients) were diagnosed with PAH over a mean (±SD) follow-up of 3.2 (±2.5) years. The incidence of PAH in this cohort was 0.7% per annum. Of these, 68.9% had limited disease subtype (lcSSc). In multivariable regression analysis, the presence of anti-centromere antibody (ACA) (OR 1.6, 95%CI 1.1–2.5, p=0.03), oesphageal stricture (OR 2.0, 95%CI 1.2–3.3, p=0.006), calcinosis (OR 1.9, 95%CI 1.2–2.9, p=0.003), sicca symptoms (OR 1.6, 95%CI 1.1–2.5, p=0.03), mild ILD (OR 2.3, 95%CI 1.5–3.7, p<0.001) and digital ulcers (OR 1.6, 95%CI 1.0–2.4, p=0.03) were predictive of PAH. This model had an area under the curve of 0.7 and concordance of 91.8%. Risk factors for PAH were were analyzed by disease subtype and are presented in Table 1 and 2. Conclusions: The incidence and prevalence of PAH in this cohort are 0.7% per annum and 8.4%, respectively. The clinical-serologic risk factors for PAH differ based on disease subtype. In both subtypes, mild ILD is associated with PAH, suggesting the possibility of a common pathogenic mechanisms underlying both of these disease manifestations. This model identifies a subset of patients at an appreciably higher risk of developing PAH, who should be screened and would in future, benefit from preventative therapies. Acknowledgement: This work was supported by Scleroderma Australia, Arthritis Australia, Actelion Australia, Bayer, CSL Biotherapies, GlaxoSmithKline Australia, Pfizer and BMS. Dr Morrisroe is a recipient of an NHMRC and RACP Shields Fellowship. Dr Nikpour holds a University of Melbourne Faculty of Medicine Dentistry and Health Science David Bickart Clinician Researcher Fellowship and is a recipient of an NHMRC Fellowship (APP1071735). Disclosure of Interest: None declared